The role of critical qualitative research in educational contexts: A Canadian perspective - Tilley, Susan (Educar em Revista, 2019)
In this paper, the author discusses the qualitative shift in educational research from a historical dependence on positivist and post-positivist frameworks to a proliferation of research situated within a qualitative, interpretivist paradigm. Offering a Canadian perspective, the author situates the discussion of critical qualitative research in relation to the growing neoliberal influence on educational contexts and policy decisions. She argues the need for educational researchers to conduct critical qualitative research to explore the complex issues that educators face to ensure that all students have access to equitable educational experiences, not only those students who represent the Canadian dominant white, middle-class norm. The author introduces a strand of qualitative research focused on the experiences of black, racialized and Indigenous students to illustrate the need for critical research that privileges local knowledge and human experience, while also taking into account the dominant institutional structures that shape educational experience. Although acknowledging the place of quantitative research in the educational domain, she argues that critical qualitative research is essential to understand the experiences of marginalized students in educational contexts and to provide space for voices not available in the quantitative domain. The author concludes that critical qualitative research has an important role to play in informing new directions in educational practices and policies that will help to ensure a socially just education for all students, regardless of backgrounds.